Factors Influencing Intention to Use Mobile Payment QR Code Among Teachers in Batu Pahat - Sariyon, Noraini; Harun, Amran; Abu Seman, Noor Aslinda (Research in Management of Technology and Business, 2020)
Mobile payment is receiving growing attention globally, from consumers to merchants, as an alternative to using cash, check, or credit cards. The potential of this technology is enormous. In this study, the focus was on mobile payment using the QR code. This study aims to determine factors that influence the intention to use mobile payment QR code. To achieve the objective, the Technology Acceptance Model (TAM), namely perceived usefulness and perceived ease of use, was employed to understand factors that influence the intention to use mobile payment. A survey method has opted through the distribution of questionnaires to 172 secondary school teachers in Batu Pahat. Data analysis was conducted using Statistical Package for the Social Sciences (SPSS) software. This study's findings showed that the teachers are ready to use the QR code for mobile payment.  Besides, perceived usefulness and perceived ease of use were positively correlated to QR code mobile payment.